Effect of Silver Nanoparticles on Growth of Eukaryotic Green Algae - Dash, Anjali; Singh, Anand P.; Chaudhary, Bansh R.; Singh, Sunil K.; Dash, Debabrata (Nano-Micro Letters, 2012)
Silver nanoparticles, endowed with powerful antimicrobial property, are the most widely used nanomaterial in consumer products, with associated risk of their easy access to environment and freshwater ecosystems by surface runoff. Although toxic effects of nanosilver on bacterial, fungal and mammalian cells have been documented, its impact on algal growth remains unknown. Pithophora oedogonia and Chara vulgaris are predominant members of photosynthetic eukaryotic algae, which form major component of global aquatic ecosystem. Here we report for the first time that nanosilver has significant adverse effects on growth and morphology of these filamentous green algae in a dose-dependent manner. Exposure of algal thalli to increasing concentrations of silver nanoparticles resulted in progressive depletion in algal chlorophyll content, chromosome instability and mitotic disturbance, associated with morphological malformations in algal filaments. SEM micrographs revealed dramatic alterations in cell wall in nanoparticle-treated algae, characterized with cell wall rupture and degradation in Pithophora. Although these observations underscore severe deleterious effects of nanosilver on aquatic environment, the information can also be exploited as a bioengineering strategy to control unwanted and persistent growth of noxious algal weeds that clog the municipal water supply and water channels and produce fouling of water bodies.